Clouds - Aristophanes,Dover, Kenneth James (Oxford University Press, 2018)
Greek text with commentary of Nubes (Clouds) by Aristophanes.
10.1093/actrade/9780198143956.book.1
Keywords: Rhetoric; Study and teaching; Drama